Stochastic Resonance in Harmonic Oscillators: Coupling Induced Dissipation and Mean Field - Singh, Aman Kumar (Discontinuity, Nonlinearity, and Complexity, 2026)
We consider coupling induced dissipation to study stochastic resonance (SR) phenomenon in a system of harmonic oscillators. Coupling through conjugate variables alludes dissipation in the coupled oscillatory systems by stabilising fixed points which are not stable in uncoupled state. We utilise this observation and investigate SR in coupled identical harmonic oscillators wherein dissipation is instigated by coupling forces. We extend the study to calculate second moment of mean field for harmonic oscillator (sixth order ode) analytically. The SR curves are also obtained numerically.